SUBTYPES OF DISABILITY AMONG OLDER PERSONS OVER THE COURSE OF NEARLY EIGHT YEARS - Gill, Thomas M. (2008)
OBJECTIVE: To characterize distinct and clinically meaningful subtypes of disability, defined on the basis of the number and duration of disability episodes, and to determine whether the incidence of these disability subtypes differ according to age, sex, and physical frailty. DESIGN, SETTING AND PARTICIPANTS: Prospective cohort study of 754 community-living residents of greater New Haven, Connecticut, who were 70 years or older and initially nondisabled in four essential activities of daily living. MEASUREMENTS: Disability was assessed during monthly telephone interviews for nearly eight years, while physical frailty was assessed during comprehensive home-based assessments at 18-month intervals. The incidence of five disability subtypes was determined within the context of the 18-month intervals among participants who were nondisabled at the start of the interval: transient, short-term, long-term, recurrent, and unstable. RESULTS: Incident disability was observed in 29.8% of the 18-month intervals. The most common subtypes were transient disability (9.7% of all intervals), defined as a single disability episode lasting only one month, and long-term disability (6.9%), defined as one or more disability episodes, with at least one lasting six or more months. About a quarter (24.7%) of all participants had two or more intervals with an incident disability subtype. While there were no gender differences in the incidence rates for any of the subtypes, differences in rates were observed for each subtype according to age and physical frailty, with only one exception, and were especially large for long-term disability. CONCLUSIONS: Our results suggest that the mechanisms underlying the different disability subtypes may differ. Additional research is warranted to evaluate the natural history, risk factors, and prognosis of the five disability subtypes.